Quantum Electrodynamics of Casimir Momentum: Momentum of the Quantum Vacuum? - Kawka, Sebastien; Bart Van Tiggelen (arXiv.org, 2009)
The electromagnetic vacuum is known to have energy. It has been recently argued that the quantum vacuum can possess momentum, that adds up to the momentum of matter. This ``Casimir momentum'' is closely related to the Casimir effect, in which case energy is exchanged. In previous theory it was treated semi-classically. We present a non-relativistic quantum theory for the linear momentum of electromagnetic zero-point fluctuations, considering an harmonic oscillator subject to crossed, quasi-static magnetic and electric and coupled to the quantum vacuum. We derive a contribution of the quantum vacuum to the linear pseudo-momentum and give a new estimate for the achievable speed. Our analysis show that the effect exists and that it is finite.